Bismarck's Shadow. - Frankel, Richard E. (Berg Publishers, 2004)
History is a tale often told by ghosts and demi-gods, and our relationship to these figures often determines the shape of the narratives we weave about the past. Bismarck's Shadow targets this idea, as it is a book that unearths a fascinating phenomenon of German political culture - the elevation of a dead political figure, Otto von Bismarck, to the level of a demi-god and the effects of such deification on the course of German politics during the first half of the 20th century.